Electrospinning of Ionogels: Current Status and Future Perspectives. Issue 7 (25th November 2014) - Taubert, Andreas
Abstract: Ionogels (IGs), also termed ion gels, are functional hybrid materials based on an ionic liquid (IL) and a polymeric, hybrid, or inorganic matrix. IGs combine the properties of the matrix such as mechanical strength with IL properties like high ionic conductivity, high thermal stability, or catalytic activity. IGs are thus attractive for many applications, but the vast majority of IGs made and published so far are bulk materials or dense films. Applications like sensing or catalysis, however, would benefit from IGs with high surface areas or defined surface morphologies or architectures. In spite of this, only relatively few examples of high‐surface‐area IGs have been made so far; this has mostly been achieved by electrospinning, which has proven to be a promising strategy towards advanced IGs. The current review discusses first developments and outlines the future potential of electrospun ionogels, predominantly from a materials and inorganic chemistry perspective. Abstract : Spin it: Electrospinning is a useful and low‐cost approach towards high‐surface‐area nanofibrous ionogels, that is, multifunctional hybrid materials based on ionic liquids, with tremendous application potential from catalysis to energy, healthcare, and beyond. The article provides an overview of the field and discusses the future potential of these promising materials.